Problem-Solution based Patent Analysis for Identifying Semiconductor Technology Trends - Mingyu Kim; Youngjin Seol; Seunghyun Lee; Janghyeok Yoon (Journal of Intellectual Property)
Semiconductor technology serves as a vital national economic asset and the foundation for advanced industries, making its trend analysis crucial for R&D strategies and technological opportunity identification. Although numerous semiconductor technology trend analyses have been conducted, systematic analysis of technology trends by linking technological problems and solutions included in patent documents to understand the context and direction of technology development remains insufficient. Therefore, this study identifies technological problems (Problem) and corresponding implementation approaches (Solution) from patent documents and proposes a Problem-Solution-based method for analyzing technology trends.